2017
DOI: 10.1007/s40145-017-0221-9
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication, mechanical properties, and tribological behaviors of Ti2AlC and Ti2AlSn0.2C solid solutions

Abstract: Highly pure and dense Ti 2 AlC and Ti 2 AlSn 0.2 C bulks were prepared by hot pressing with molar ratios of 1:1.1:0.9 and 1:0.9:0.2:0.85, respectively, at 1450 ℃ for 30 min with 28 MPa in Ar atmosphere. The phase compositions were investigated by X-ray diffraction (XRD); the surface morphology and topography of the crystal grains were also analyzed by scanning electron microscopy (SEM).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 30 publications
(67 reference statements)
4
18
0
Order By: Relevance
“…It is worth noticing that the measured grain size of materials prepared by two‐time HP was significant decreased. For Ti 2 AlC, the grain size is around 9.1 μm in length and 4 μm in width in this work, comparatively, the average grains size of the Ti 2 AlC was estimated to be ~20 μm in length and ~8 μm in width for in situ hot pressing method and ~20 μm in length and ~5 μm in width for SPS, showing a declining tendency. The grain refinement mechanism appears to play a role in the performance improvement of materials synthesized by two‐time HP, which can partially explain the higher strength and hardness values of Ti 2 AlC in this work.…”
Section: Resultsmentioning
confidence: 49%
See 2 more Smart Citations
“…It is worth noticing that the measured grain size of materials prepared by two‐time HP was significant decreased. For Ti 2 AlC, the grain size is around 9.1 μm in length and 4 μm in width in this work, comparatively, the average grains size of the Ti 2 AlC was estimated to be ~20 μm in length and ~8 μm in width for in situ hot pressing method and ~20 μm in length and ~5 μm in width for SPS, showing a declining tendency. The grain refinement mechanism appears to play a role in the performance improvement of materials synthesized by two‐time HP, which can partially explain the higher strength and hardness values of Ti 2 AlC in this work.…”
Section: Resultsmentioning
confidence: 49%
“…The values of density, grain size, Vickers hardness, flexural strength and fracture toughness of the produced Ti 2 AlC and Ti 2 Al 0.8 Sn 0.2 C are shown in Table . The properties of Ti 2 AlC and Ti 2 Al 0.8 Sn 0.2 C prepared by in situ hot pressing method in our former work and by other methods in references are also listed for comparison. Observing that the Vickers hardness and flexural values of bulk materials increase significantly compared to materials prepared using in situ hot pressing method, the Vickers hardness values are enhanced by approximately 20% for both Ti 2 AlC and Ti 2 Al 0.8 Sn 0.2 C, and the value error of hardness gets smaller, indicating that the materials are more homogeneous and highly relative dense, the flexural strength value of Ti 2 AlC is enhanced by 51% and that of Ti 2 Al 0.8 Sn 0.2 C is enhanced by 27%.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nowadays, intensive studies indicated that substitution on M, A, or X site in MAX phases could improve mechanical properties of the MAX phases . The Vickers hardness of (Cr 1− x V x ) 2 AlC increased linearly with V content due to solid solution hardening.…”
Section: Introductionmentioning
confidence: 99%
“…In the past 10 years, many studies have been conducted on the tribological studies of MAX phases such as Ti 3 SiC 2 , Ti 3 AlC 2 , and MAX matrix composites. [] Incorporating the SiC fibers into Cr 2 AlC matrix can reduce the friction coefficient by 20%, whereas the wear resistance of Cr 2 AlC/10 SiC composite improved by 70%‐80%. Ta 2 AlC, Ta 2 AlC/Ag, and Cr 2 AlC/Ag composites were tested against Ni‐based superalloy, the self‐generated films of MAX phase and MAX matrix composite mainly determined the tribological properties.…”
Section: Introductionmentioning
confidence: 99%